Corporate donations and shareholder value - LIANG, Hao (Institutional Knowledge at Singapore Management University, 2017)
Do corporate donations enhance shareholder wealth or reflect agency problems? We address this question for a global sample of firms whereby we distinguish between charitable and political donations, as well as between donations in cash and in kind. We find that charitable donations are positively related to financial performance and firm value, which is consistent with the value-enhancement hypothesis. This positive effect on firm value is stronger for cash than in-kind donations. In contrast, political donations do not appear to enhance shareholder value, but rather tend to reflect agency problems, as they are higher for firms with poor internal corporate governance and strong managerial entrenchment. We address endogeneity concerns by using peer firms’ donations as an instrument in a two-stage least squares (2SLS) setting and by conducting a difference-indifference analysis around a general election.